2018
DOI: 10.1002/anie.201800660
|View full text |Cite
|
Sign up to set email alerts
|

Lead‐Free Silver‐Bismuth Halide Double Perovskite Nanocrystals

Abstract: Lead-free perovskite nanocrystals (NCs) were obtained mainly by substituting a Pb cation with a divalent cation or substituting three Pb cations with two trivalent cations. The substitution of two Pb cations with one monovalent Ag and one trivalent Bi cations was used to synthesize Cs AgBiX (X=Cl, Br, I) double perovskite NCs. Using femtosecond transient absorption spectroscopy, the charge carrier relaxation mechanism was elucidated in the double perovskite NCs. The Cs AgBiBr NCs exhibit ultrafast hot-carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
322
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(343 citation statements)
references
References 48 publications
17
322
0
4
Order By: Relevance
“…[160] In the absence of other limiting photophysical properties exhibited by this compound, such excellent charge transport properties could make it endure higher film thickness with enhanced light absorption and higher PV performance. In a similar report, [163] femtosecond transient absorption spectroscopy was used to elucidate the charge carrier relaxation mechanism in Cs 2 AgBiBr 6 NCs. The decays in the PL spectra matched the rise in an excited state on a microsecond timescale.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 2 more Smart Citations
“…[160] In the absence of other limiting photophysical properties exhibited by this compound, such excellent charge transport properties could make it endure higher film thickness with enhanced light absorption and higher PV performance. In a similar report, [163] femtosecond transient absorption spectroscopy was used to elucidate the charge carrier relaxation mechanism in Cs 2 AgBiBr 6 NCs. The decays in the PL spectra matched the rise in an excited state on a microsecond timescale.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Conversely, Li et al proposed an In 3+ poor and Cl − rich growth condition to realize suppressed and shallow level defects in the Cs 2 AgInCl 6 analog. [163] Copyright 2018, Wiley-VCH. Particularly, Cu +based halide double perovskites such as Cs 2 CuInCl 6 have been Figure 5.…”
Section: + /In 3+ Halide Double Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…But it was usually used as absorber of the solar cell rather than the light‐emitting device . Up to now, several studies have reported the synthesis of colloidal double perovskite NCs including Cs 2 AgBiX 6 (X = Cl, Br, and I), Cs 2 AgSb 1− y Bi y X 6 (X = Br and Cl; 0 ≤ y ≤ 1) and Cs 2 AgIn x Bi 1− x Cl 6 ( x = 0, 0.25, 0.5 0.75, and 0.9) NCs . The reported highest PLQY is ≈36.6% .…”
mentioning
confidence: 99%
“…Stability tests show that, when exposed to air and light for 6 weeks, films of Cs 2 AgBiBr 6 NCs exhibit some decomposition, while films of Cs 2 AgBiI 6 NCs fully decompose within 3 days. Cs 2 AgBiX 6 NCs were also obtained via direct synthesis by an anti‐solvent recrystallization . The obtained Cs 2 AgBiI 6 NCs were found to be stable in nanostructures, but no further investigations are available.…”
Section: Lead‐free Halide Perovskite Nanocrystals: Synthesis Stabilimentioning
confidence: 99%